Perencanaan Pembangunan Smoking Area di Gedung Bitumen Pertamina Gresik Menggunakan Critical Path Method (CPM) - Enrico Ferdiansyah; Erni Puspanantasari Putri (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Bitumen Plant Gresik operated by PT Pertamina Patra Niaga does not yet have a dedicated smoking area at its office, despite the oil and gas environment carries a high fire risk. This study aims to plan the smoking area construction using the Critical Path Method (CPM) supported by Microsoft Project to determine the duration, critical path, and total project cost. The data used cover 20 work activities along with their durations, predecessors, volumes, and unit prices. Results show the project duration is 59 calendar days (1 February to 31 March 2026), with three parallel critical paths covering foundation, column, roster, flooring, anti-heat sticker, decorative elements, and site cleaning. The total project cost reaches IDR 255,850,000 (excluding 11% VAT), with the largest share of 84.53% allocated to structural and architectural work. These findings may serve as a project control baseline in oil and gas industrial settings.